2011
DOI: 10.1007/s00540-011-1199-z
|View full text |Cite
|
Sign up to set email alerts
|

Propofol protects against impairment of learning-memory and imbalance of hippocampal Glu/GABA induced by electroconvulsive shock in depressed rats

Abstract: The data suggest that propofol alleviated ECS-induced learning-memory impairment without interfering with the antidepressant efficacy of ECS, possibly by inhibiting excessive expression of GAD65 and maintaining the balance between glutamatergic and GABAergic amino acids neurotransmitters in the hippocampus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 35 publications
3
33
0
1
Order By: Relevance
“…Complex neurophysiological and neurobiochemical mechanisms are involved in learning and memory processes, and the mechanisms are closely related, not only to the central cholinergic nervous system, but also to central amino acid neurotransmitters. Asparaginate (Asp) and Glu are excitatory amino acids and Gly and GABA are inhibitory amino acids, which play important roles in maintaining the balance of excitation and inhibition in the central nervous system (Luo et al, 2011;Wang et al, 2014). Changes in the level of central amino acids in AD, especially the imbalance between Glu and GABA, are key factors leading to neuron injury (Cui et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Complex neurophysiological and neurobiochemical mechanisms are involved in learning and memory processes, and the mechanisms are closely related, not only to the central cholinergic nervous system, but also to central amino acid neurotransmitters. Asparaginate (Asp) and Glu are excitatory amino acids and Gly and GABA are inhibitory amino acids, which play important roles in maintaining the balance of excitation and inhibition in the central nervous system (Luo et al, 2011;Wang et al, 2014). Changes in the level of central amino acids in AD, especially the imbalance between Glu and GABA, are key factors leading to neuron injury (Cui et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was further demonstrated that propofol reversed the elevated expression of hippocampal glutamic acid decarboxylase 65 (GAD 65) induced by electroconvulsive shock in depressed rats. GABA production pathway in the brain uses glutamate substrate and GAD as a catalyst, whereby GAD 65 is GAD catalyst 61 . Thus explaining the protective effects of propofol.…”
Section: Prevention Of Neurocognitive Side-effect Of Electroconvumentioning
confidence: 99%
“…Phosphorylation of Tau protein leads to reduced axonal transport efficiency thereby impairing neural signal transmission and causing neuron apoptosis or death and eventually leading to impairment of learning and memory. Gang Liu et al proved that ECT-induced stress increases hippocampal Glu concentration and Tau protein phosphorylation leading to learning and memory impairment and is clearly associated with the current and duration of ECT .Previous studies have shown that electroconvulsive seizure for 120-180sec can lead to cognitive disorders 60 due to pathological dysfunction of the glutamic acid (Glu) signalling system 61,62,63 . Glu, an excitatory neurotransmitter transmits ~40% of synapses leading to oxidative stress 64 , causing hippocampal indiscrimination's and saturated long-term potentiation (LTP) 62 , resulting in synaptic plasticity deterioration 63 and The Akt Pathway or PI3K-Akt Pathway, a signal transduction pathway responsible for the promotion of survival and growth in response to extracellular signals and its main protein includes PI3K (phosphatidylinositol 3-kinase) and Akt (Protein Kinase B).…”
mentioning
confidence: 99%
“…an increase in GABA and a decrease of GLU levels) in the hippocampus of rats. [23,24] In fact, this measure of the GABAergic tone appears to be more informative than single neurotransmitter levels, given that GLU (a precursor of GABA) and GABA exert their effects in a neuromodulatory conjunction. [25] Similar findings were observed in humans.…”
Section: Gaba In Mdsmentioning
confidence: 99%